Identity and feminine life in the novel "A Secret in the Alleys" - mitra farara; najmeh nazari; Esmaeel Balali; galavizh alizadeh (زن در فرهنگ و هنر)
The revision of Feminine identity has been influenced by the acceleration of globalization and modernization, as well as the connection of Iranian women with the modern world and the social developments in Iran over the past century. The societal and literary manifestations of Iranian women's reevaluation of their individual and social identities are evident in the last few decades. Fariba Vafi is one of the successful Iranian story writers. The Iranian woman's identity is one of Vafi's concerns in his works, such as the novel "A Secret in the Alleys. The current research, which employs a descriptive-analytical approach, examines the components of female identity and life in this novel .It also addresses issues such as identity crisis, the transition between modern and traditional identity, and the retrieval and revision of feminine identity. It identifies the underlying factors, including aspirations, emotions, needs, and desires and women’s reactions to various circumstances. In this novel, along with narrating the three generations of women's lives, the author deals with female identity and its related topics, such as identity crisis, recovery and revision of female identity, and Iranian women's transition from traditional identity to modern identity. The novel is characterized by the pervasive presence of various forms of violence, particularly directed at women by males. In this novel, the author critiques the dominant gender stereotypes and ideology of society and emphasizes the necessity of reevaluating the identity of women and their role and position in the family and society, with awareness and to avoid extremes.